Telling and Being Told : Storytelling and Cultural Control in Contemporary Yucatec Maya Literatures - Worley, Paul M., 1976- (Book collections on Project MUSE., 2013)
Through performance and the spoken word, Yucatec Maya storytellers have maintained the vitality of their literary traditions for more than five hundred years. This book presents the figure of the storyteller as a symbol of indigenous cultural control in contemporary Yucatec Maya literatures. Analyzing the storyteller as the embodiment of indigenous knowledge in written and oral texts, this book highlights how Yucatec Maya literatures play a vital role in imaginings of Maya culture and its relationships with Mexican and global cultures.